Functional difference between Thy-1-positive and Thy-1-negative gamma delta T cells induced by Escherichia coli infection in mice. - Takada, H (1996)
There is an increase in number of gamma delta T cells in the peritoneal cavity after intraperitoneal (i.p.) inoculation with Escherichia coli. The E. coli-induced gamma delta T cells in C3H/He mice contain a large amount of Thy-1-negative population in addition to the Thy-1-positive population. We investigated the difference between the Thy-1-positive and the Thy-1-negative gamma delta T cells. Although it was found that only up to 4% of the gamma delta T cells on day 5 after infection were in cycling phase, and that the gamma delta T cells did not proliferate by immobilized anti-T-cell receptor (TCR) gamma delta monoclonal antibody stimulation, the gamma delta T cells proliferated in the presence of interleukin-2 (IL-2) and IL-7. The Thy-1-negative gamma delta T cells showed higher proliferative response compared with the Thy-1-positive gamma delta T cells. Furthermore, the Thy-1-negative gamma delta T cells showed lower IFN-gamma mRNA expression than the Thy-1-positive gamma delta T cells. On the other hand, both the Thy-1-positive and Thy-1-negative gamma delta T cells predominantly expressed V gamma 1, V gamma 4, V gamma 5, V gamma 6 and V delta 1, and no difference of V region usage was detected between them. These results suggest that functions of Thy-1-positive gamma delta T cells differ from Thy-1-negative gamma delta T cells although Thy-1-positive and Thy-1-negative gamma delta T cells may have similar V region repertoire and, possibly, similar antigen specificity.